The pedagogical workshop "Perceptions and feelings of people with disabilities about the world of work" and the "efficient" application (Research, Society and Development, 2021)
In order to understand how people with disabilities (PcD) access to work occur, this article aims to present the results of the application of a pedagogical workshop for students and former students with disabilities from the Federal Institute of Piauí-IFPI (Teresina-Central), where this educational proposal was sought to reveal the perception of people with disabilities (PcD) about the world of work. reflect issues that involve the difficulties of access and permanence of PCD sat in labor activities, as well as discuss labor laws that support people with disabilities and present a technological tool the application "Efficient" that aims to give more autonomy and agility to job vacancies that are reserved for this public. The proposal of this research is found in the profile of action research supported by the qualitative methodology, where it was proposed to investigate the difficulties of insertion in the world of work of people with disabilities, using semi-structured questionnaires applied at each stage for data production. The results showed that the pedagogical workshop brought significant reflections contributing to the formation of PCD, bringing relevant discussions related to the insertion to the world of work, also revealing the importance of using technology as a facilitator to the inclusion of people with disabilities.